Realising organizational overall benefits from ERP (Enterprise resource planning): Which stage is important? - Tran Thi Cam Thanh - Dao Nhat Minh - Do Hoang Nhat Yen (My University, 2018)
Realising organizational overall benefits from ERP (Enterprise resource planning): Which stage is important?
Keywords: ERP benefits; Organizational benefits; Stages